Clinical manual of addiction psychopharmacology - Kranzler, Henry R., 1950-; Ciraulo, Domenic A.; Zindel, Leah R., 1959- (American Psychiatric Publishing, 2014)
This book offers a comprehensive, meticulously detailed review of the pharmacology of addictive drugs and the medications used to treat abuse of and dependence on these addictive drugs. Though rich in detailed background, it is written with a therapeutic focus, as a clinical guide for the use of pharmacotherapy in patients with substance use disorders. Experts cover all major classes of substances that are clinically important in relation to addiction.